Perspektif Regulatory Impact Assessment (RIA) dalam Kajian Kebijakan: Studi Kasus Peraturan Ganjil-Genap di DKI Jakarta - Zulatsari, Anindya Atma; Firman Sampurna, Agung (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
Regulatory Impact Analysis (RIA) is an important instrument for policy designers to master in order to calculate the costs that may be borne and the benefits that can be obtained in implementing policies. RIA is important to assist policy makers in the decision-making process. One of the government policies that can be implemented by RIA analysis is the policy of implementing odd-even rules on a number of arterial roads carried out by the Special Capital Region (DKI) Jakarta Government. This policy limits motorized vehicles based on vehicle registration numbers as a solution to dealing with pollution problems in the capital. Alternative policies has emerged, such as Electronic Road Pricing (ERP) which will be analyzed using RIA with the Cost-Benefit Analysis (CBA) method demonstrating high Benefit-Cost Ratio (BCR) than other alternatives in the long term. Thus, if the ERP policy is implemented, the goal of reducing air pollution problem in DKI Jakarta will be achieved.